Epithelial-mesenchymal interconversions in ovarian cancer: the levels and functions of E-cadherin in intraabdominal dissemination - Ricardo J. Roque; Margarida Figueiredo Dias; Filipa Costa Sousa (Frontiers Media S.A., 2020)
The metastatic process of ovarian cancer (OC) is almost exclusively defined by direct shedding of tumor cells into the abdominal cavity, followed by clustering into multicellular aggregates and posterior peritoneal anchorage. This process relies on dynamic intercellular interactions which are modified by epithelial-mesenchymal interconversions and, therefore, E-cadherin expression variability. Although widely accepted as a tumor suppressor in many types of cancer, E-cadherin is currently known to have a dynamic expression and a much more complex role in OC. First, high E-cadherin expression is considered a sign of metaplasia in the normal ovarian epithelium, due to its association with epithelial growth factor receptor (EGFR) mediated cell proliferation. Subsequently, it is the decreased expression of E-cadherin that allows the acquisition of a more invasive phenotype, leading to the spread of primary tumor cells into the peritoneal fluid. This downregulation seems to depend on complex regulatory mechanisms, from molecular proteolysis to microenvironment interference and epigenetic regulation. E-cadherin cleavage and its resulting fragments appear to be essential to the process of dissemination and even to the formation of multicellular aggregates. Paradoxically, the maintenance of some E-cadherin expression seems to promote intercellular adhesion, resistance, and survival while decreasing cancer response to chemotherapy. Multiple studies have shown that reversing epithelial-mesenchymal transaction (EMT) and increasing E-cadherin expression prevents OC intraperitoneal dissemination, but findings that simultaneously correlate E-cadherin downregulation to higher chemotherapy sensitivity should not be ignored. Nevertheless, EMT and E-cadherin seem to have a potential interest as therapeutic targets in novel approaches to OC treatment.